Histochemical Examination on Periodontal Tissues of Klotho-Deficient Mice Fed With Phosphate-Insufficient Diet. (April 2017) - Hikone, Kumiko; Hasegawa, Tomoka; Tsuchiya, Erika; Hongo, Hiromi; Sasaki, Muneteru; Yamamoto, Tomomaya; Kudo, Ai; Oda, Kimimitsu; Haraguchi, Mai; de Freitas, Paulo Henrique Luiz; Li, Minqi; Iida, Junichiro; et al.
To elucidate which of elevated serum concentration of inorganic phosphate (Pi) or disrupted signaling linked to αklotho/fibroblast growth factor 23 (FGF23) is a predominant regulator for senescence-related degeneration seen in αKlotho -deficient mice, we have examined histological alteration of the periodontal tissues in the mandibular interalveolar septum of αKlotho -deficient mice fed with Pi-insufficient diet. We prepared six groups of mice: wild-type, kl/kl, and αKlotho −/− mice with normal diet or low-Pi diet. As a consequence, kl/kl norPi and αKlotho −/−norPi mice showed the same abnormalities in periodontal tissues: intensely stained areas with hematoxylin in the interalveolar septum, dispersed localization of alkaline phosphatase–positive osteoblasts and tartrate-resistant acid phosphatase–reactive osteoclasts, and accumulation of dentin matrix protein 1 in the osteocytic lacunae. Although kl/kl lowPi mice improved these histological abnormalities, αKlotho −/− lowPi mice failed to normalize those. Gene expression of αKlotho was shown to be increased in kl/kl lowPi specimens. It seems likely that histological abnormalities of kl/kl mice have been improved by the rescued expression of αKlotho, rather than low concentration of serum Pi. Thus, the histological malformation in periodontal tissues in αKlotho -deficient mice appears to be due to not only increased concentration of Pi but also disrupted αklotho/FGF23 signaling.